2023
DOI: 10.1182/bloodadvances.2023011041
|View full text |Cite|
|
Sign up to set email alerts
|

International study of treatment efficacy in SS shows superiority of combination therapy and heterogeneity of treatment strategies

Belinda A. Campbell,
Gabor Dobos,
Zahra Haider
et al.

Abstract: Despite increasing availability of therapies, patients with Sezary syndrome (SS) commonly endure multi-line treatment journeys, mostly with partial responses of short duration. Measuring clinical benefit is challenging; time-to-next-treatment (TTNT) provides a robust, objective measurement of efficacy. This international observational study, from three quaternary centers, examines patterns of clinical care and therapeutic benefit as measured by TTNT. TTNT was calculated for monotherapies and combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
2
6
2
Order By: Relevance
“…In our study, retinoids were primarily used as first-line therapy, comprising 65% of cases, and were commonly employed across all treatment regimens, either alone (45%) or in combination with ECP (58%). TTNT for all retinoids was 5.85 months, which was higher than the 4.4 months reported in another study [ 14 ]. When retinoids were used in combination therapy with ECP, the TTNT was 6.38 months, and in combination with IFN-α, this extended to 14.14 months.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In our study, retinoids were primarily used as first-line therapy, comprising 65% of cases, and were commonly employed across all treatment regimens, either alone (45%) or in combination with ECP (58%). TTNT for all retinoids was 5.85 months, which was higher than the 4.4 months reported in another study [ 14 ]. When retinoids were used in combination therapy with ECP, the TTNT was 6.38 months, and in combination with IFN-α, this extended to 14.14 months.…”
Section: Discussioncontrasting
confidence: 69%
“…The initial management of SS patients varies, as there are several treatment options [ 14 , 42 ]. The median duration of all treatments among our patients was 5.88 months, which is consistent with previous reports [ 14 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that combining ECP with complementary therapies may lead to better response rates [ 12 , 31 ]. Also, it appears that patients benefit from early inclusion of ECP to their treatment regime [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Campbell et al demonstrated that first-line combination therapies have a longer time to next treatment (TTNT) than monotherapies and that patients benefit from an early inclusion of ECP in their therapeutic algorithm [ 17 ].…”
Section: Introductionmentioning
confidence: 99%